VALORIZATION OF AVOCADO SEED RESIDUE AS BIOMASS FOR BIOSYNGAS PRODUCTION VIA OPTIMIZED STEAM GASIFICATION PROCESS USING BOX-BEHNKEN DESIGN (BBD) APPROACH - Mohammed, Jibrin; Madaki, Kabiru S.; Ibrahim, Jafar A. (FUDMA Journal of Sciences, 2026)
ABSTRACT Sustainable conversion of agricultural residues into renewable fuels is critical for addressing global energy and environmental challenges. This study investigates the potential of avocado seed residue (ASR), a lignocellulosic by-product of oil extraction, as a feedstock for biosyngas production via optimized steam gasification using Box-Behnken design (bbd) approach.The physicochemical and elemental compositions of ASR were assessed using standard analytical procedures, which revealed favorable properties for biosyngas production. Gasification experiments were conducted in a laboratory-scale bubbling fluidized bed reactor, and process optimization was performed using the Box-Behnken Design approach. The effects of temperature, steam-to-biomass ratio (S/B), and particle size on hydrogen (H₂), carbon monoxide (CO), and methane (CH₄) yields were systematically analyzed and indicated a strong influence on the yields. Analysis of variance (ANOVA) confirmed the significance and predictive accuracy of the quadratic models (p < 0.0001, R² > 0.97). Maximum yields of 30.76 vol% H₂, 11.35 vol% CO, and 11.00 vol% CH₄ were achieved at 900 °C, S/B ratio of 0.6, and particle size of 2.5 mm, with a very close agreement between predicted and experimental values (deviation <2%), which further confirms the reliability of the developed models. The findings demonstrated that ASR is a promising feedstock for efficient biosyngas generation, and that RSM-BBD provides a reliable technique for optimizing gasification parameters for maximum yield of biosyngas from the avocado seed residue.